Estudio de factibilidad para la creación de una empresa especializada en el servicio de limpieza de viviendas, oficinas y locales comerciales en el cantón Balzar, año 2013. - Martínez Burgos, Jéssica Tatiana (2015)
The business activity is to provide a specialized cleaning service, so you should create a company under administrative guidelines allowing to carry out a feasibility study for the fulfilment of the objectives. offices and commercial premises in Canton Balzar, which allowed the application of different methods and sources of information. The market study in the Canton Balzar, with a sample of 239 families; Weighted survey the target market is determined, therefore it was established in this favorable reception canton since 94% of respondents consider it very important that there is a company that provides cleaning services to homes, offices and local commercial…..